Betrayal [large type] - Hatcher, Robin Lee (Hatcher, Robin Lee. Where the heart lives., 2013)
"It's the turn of the twentieth century and drifter Hugh Brennan is a man well acquainted with betrayal. Hugh finds himself drawn to the attractive widow, Julia, yet when he looks into her eyes, he recognizes the same hurt that haunts him. Julia Grace has little reason to trust men, but she's going to have to trust someone if she's to keep her ranch from the clutches of her dead husband's half-brother. Is it possible God had a hand in bringing Hugh to her door? The latest historical romance from award-winning author Robin Lee Hatcher and the second book in the Where the Heart Lives series, Betrayal will take you to the high desert of western Wyoming, through the crags of the Rocky Mountains, and into the hearts of two seekers learning to trust God's love no matter the circumstances" -- Cover verso.